Affective and Territorial Polarisation: The Impact on Vote Choice in Spain. Issue 1 (2nd January 2022) - Rodon, Toni
ABSTRACT: What is the effect of affective polarisation on vote choice? Despite the growing interest in affective polarisation, scholars still do not fully understand the relationship between partisan affective polarisation and political behaviour. Crucially, most existing studies have assumed, often by default, that affective polarisation mainly occurs along a single politicised partisan identity. This article addresses the hitherto neglected relationship between affective polarisation and vote choice in Spain, where distrust between different and opposite groups occurs both on ideological and territorial terms. Using rich panel data, the study findings show that both affective polarisation types are significant predictors of vote choice. While affectively partisan-polarised voters are more likely to support the left, affectively polarised voters on the territorial dimension are more likely to support the right.